A Dynamic Utility Adaptation Framework for Efficient Multimedia Service Support in CDMA Wireless Networks. (29th May 2010) - Kastrinogiannis Kastrinogiannis, Timotheos Timotheos; Papavassiliou Papavassiliou, Symeon Symeon
Abstract : In this paper the problem of channel-aware opportunistic resource allocation for the downlink in CDMA wireless networks supporting simultaneously real-time multimedia and non-real-time data services is addressed. In order to treat different types of services with diverse QoS prerequisites through common optimization formulation a utility-based power and rate allocation framework is adopted. Emphasis is placed on real-time services' strict short-term QoS prerequisites, the fulfillment of which requires a significantly different treatment than the use of static utility functions, traditionally used to address long-term QoS or fairness prerequisites of delay-tolerant data services. To that end, we introduce a novel framework that enables the dynamic adaptation of real-time multimedia users' utilities as the system evolves, with respect to the corresponding short-term throughput service performance variations. The corresponding non-convex network utility maximization (NUM) problem is then formulated and solved, to obtain optimal power and rate allocation. Via simulation and analysis it is demonstrated that significant performance improvements are achieved in terms of real-time user's short-term throughput requirement satisfaction, without any considerable loss in total system throughput. Finally, essential tradeoffs between fulfilling real-time services' short-term QoS prerequisites and maximizing system performance, under an opportunistic scheduling wireless environment, are revealed and quantified.